Efeitos renoprotetores da ativação da ECA2 na lesão renal aguda induzida por gentamicina em ratos - Tatiane Cristine Silva de Almeida (2017)
Acute kidney injury (AKI) is an important global public health problem. Thus, efforts to reduce its impact are of paramount importance. The renin-angiotensin system (RAS) plays a critical role in the progression of renal injury. Indeed, the axis composed by angiotensin-converting enzyme (ACE) 2, Angiotensin (Ang)(1-7) and Mas receptor is able to modulate the renal function. Recent studies have shown that ACE2 activation using the compound diminazene aceturate (DIZE) causes beneficial effects in the cardiovascular and renal systems. The current study evaluated the actions of DIZE used preventively or therapeutically in an acute renal injury model induced by gentamicin (GM) in rats. The experimental protocol lasted 15 days, in which male Wistar rats were initially divided into 5 experimental groups composed by 7animals each: Control/Saline, Control/DIZE, GM/Saline, Therapeutic and Preventive. The animals were placed in metabolic cages for 3 days for an adaptation period. From day 4 today 8, 2 daily doses of GM (80 mg/kg/day, 0.1 mL/100 g) were administered in animals of the GM/Salina, Therapeutic and Preventive groups for AKI induction. The other groups received 0.9%NaCl. Treatment with DIZE (1 mg/kg by gavage) started on the 4thday in animals of the Preventive group and on the 9th day in animals ofthe Control/DIZE and Therapeutic groups. Control rats received 0.9%NaCl. Blood and urine samples were collected on days 4 and 9 and at the end of the proposed protocol. At the end of the experimental protocol, the animals were euthanized and kidney samples were collected. Renal function analysis showed that DIZE treatment (Preventive and Therapeutic groups) improved the following renal parameters at the proposed time points (5thand 15th days): serum creatinine, glomerular filtration rate (GFR) and proteinuria. No significant changes were observed in urine volume, urine osmolality, water excretion fraction, osmolar clearance, water balance, kidney weight, body weight and NGAL compared to GM/Salina group. GM did not alter water intake and plasma osmolality. When administered preventively, DIZE modulated the inflammatory profile, reducing the renal cytokines levels of IL-1β, TNF-, IL-6 and increasing IL-10. Also, it was evidenced a decrease in NAG and MPO activity in the Preventive group. The renal tissue morphometry showed a decreased number of inflammatory cells in the Preventive andTherapeutic groups. Renal histology analysis confirmed the presence of tubular lesion in the GM/Saline group and an improvement of this condition in animals treated with DIZE. DIZE administration reduced the urinary levels of ACE and Ang II in both treatments. In relation to Ang-(1-7) urinary concentration, an increase was observed in the Preventive group (5th day) and in the Therapeutic group (15th day), followed by a decrease in the Preventive group (15th day). No significant alterations were observed in the ACE2 levels. Overall, these findings suggest that ACE2 activation is a feasible strategy to prevent and treat AKI.